Mycophenolate mofetil: an update on its mechanism of action and effect on lymphoid tissue - Krawczyk, Anna; Kravčenia, Bernard; Maślanka, Tomasz (Frontiers in Immunology, 2025)
IntroductionMycophenolate mofetil (MMF) is an immunosuppressive drug administered in the management of both autoimmune diseases and organ transplantation. The main aims of the study were: (a) to obtain information regarding the safety of using MMF in respect of its effect on normal T and B cells in lymphoid tissues; (b) to investigate whether the generation of inducible Foxp3-expressing regulatory T cells (Treg) might constitute additional mechanisms underlying the immunosuppressive properties of MMF.MethodsThe effect of MMF (in vivo studies) and its active metabolite, mycophenolic acid, (in vitro studies) on murine CD4+ and CD8+ T cells as well as B cells was determined, regarding: (a) absolute count, proliferation and apoptosis of these cells (in vitro studies); (b) absolute count of these cells in the head and neck lymph nodes, mesenteric lymph nodes and the spleen (in vivo studies).ResultsThe study found that the treatment of mice with MMF induced depletion of CD4+ and CD8+ T cells and B cells in lymph nodes and the spleen, and the magnitude of these effects should be considered as clinically relevant. The study demonstrated the following actions of the drug: (a) proapoptotic action on effector CD4+ and CD8+ T (Teff) cells, and B cells; (b) the down-regulation or prevention of activation-induced expression of CD25 on CD4+ and CD8+ Teff cells; (c) the generation of Foxp3+CD25+CD4+ and Foxp3+CD25+CD8+ T cells resulting in the shift of the Treg cell/activated Teff cell balance toward an increased proportion of Treg cells.ConclusionThe depletive effect of MMF on CD4+ and CD8+ T cells and B cells in lymphoid tissues should be taken into account when assessing the benefit-risk ratio of using MMF in patients with microbial infections and undergoing vaccination. The study contributed new insight into this mechanism, indicating that MMF effectively prevents the proliferation of T and B cells, but may be less effective against already proliferating cells. Moreover, the findings of the study strongly suggest the existence of additional mechanisms that may be responsible for the clinical efficacy of the drug, including the induction of Foxp3-expressing CD4+ and CD8+ Treg cells.